A novel sodium carboxymethyl ellulose/aluminium citrate gel for extinguishing spontaneous fire in coal mines. (29th May 2018) - Zhou, Chunshan; Tang, Yibo
Summary: Spontaneous combustion of coal is one of the main disasters affecting safe production in mines. A sodium carboxymethyl cellulose/aluminium citrate gel for prevention and extinguishing of mine fires was prepared. Based on a temperature‐controlled experiment, the authors studied the influences of the gel on indicator gases generated in the spontaneous combustion of coal, crossing point temperature, and activation energy. The results showed that the crossing point temperature of coal samples treated by the gel increased by more than 13.9°C and the activation energy rose by 7.17 to 16.34%. Moreover, the indicator gases, such as CO and C 2 H 4 generated in the oxidation, decreased significantly. After treatment with the gel, the weight loss rate of the coal samples was reduced, and less energy was released. By using the self‐developed test platform (coal capacity of 2 m 3 ), the spontaneous combustion of coal on the roof of a roadway was simulated, and the carboxymethyl cellulose/aluminium citrate gel was used for fire extinguishing. After injecting the gel, the temperature in the furnace rapidly decreased, and the concentration of O 2 remained at less than 3%, without showing any after‐combustion effects.